Investigating Mental Health Implications for Drug Court Participants - Humenik, Alexis M. (International journal of offender therapy and comparative criminology, 2021)
Drug Court Treatment (DCT) Programs seek to integrate substance abuse treatment into the criminal justice system by providing a structured environment for offenders who engage in treatment in lieu of incarceration. DCT has shown successes in reducing drug/alcohol use, recidivism, and cost, but the impact of DCT on non-substance-related mental health outcomes is less clear. This study evaluated mental health correlates within a DCT sample through analyses of participants’ pre-entry and pre-graduation Minnesota Multiphasic Personality Inventory—Second Edition (MMPI-2) profiles. When diagnostic information was available, mood disorders had the highest comorbidity with alcohol/substance use diagnoses. Comparisons across administrations of the MMPI-2 indicated significant differences among mean scores on 6 Clinical scales, and mean profile elevation scores significantly decreased. Results suggest a significant presence of mental health comorbidities in DCT programs, and significant mental health improvements were seen for graduates, suggesting the utility of DCT for treating mental health problems in addition to substance use.